2021
DOI: 10.3389/fphys.2021.683025
|View full text |Cite
|
Sign up to set email alerts
|

HADLN: Hybrid Attention-Based Deep Learning Network for Automated Arrhythmia Classification

Abstract: In recent years, with the development of artificial intelligence, deep learning model has achieved initial success in ECG data analysis, especially the detection of atrial fibrillation. In order to solve the problems of ignoring the correlation between contexts and gradient dispersion in traditional deep convolution neural network model, the hybrid attention-based deep learning network (HADLN) method is proposed to implement arrhythmia classification. The HADLN can make full use of the advantages of residual n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Some studies detect AF from a single‐lead ECG (M. Jiang et al, 2021; Z. Li, Feng, et al, 2019; Yu et al, 2022; O. Zhang, Ding, et al, 2021). Fang et al (2023) developed a dual‐channel neural network for AF detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies detect AF from a single‐lead ECG (M. Jiang et al, 2021; Z. Li, Feng, et al, 2019; Yu et al, 2022; O. Zhang, Ding, et al, 2021). Fang et al (2023) developed a dual‐channel neural network for AF detection.…”
Section: Resultsmentioning
confidence: 99%
“…Their analysis highlighted that the simple model remained the gold standard for risk prediction of AF. M. Jiang et al (2021) created a convolutional neural network predicting AF recurrence risk post‐catheter ablation using 12‐lead ECG data. Using a multi‐modal ML approach incorporating ECG and cardiac imaging data (radiomics), Pujadas et al (2022) reported better AF prediction than models using ECG features alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the attention mechanism has been introduced [ 55 ] to improve the performance of deep learning models; it highlights the more informative feature and subsequently gives higher weights to the corresponding original feature sequence. It has been embedded with the LSTM architecture in several EEG studies [ 21 , 28 , 48 , 61 , 62 , 66 , 67 ] by effectively selecting the feature information and observed with significantly improved efficiency and performance accuracy of deep learning systems.…”
Section: Introductionmentioning
confidence: 99%
“…The interest to the AF detection problem is intensified during the last three years after the Challenge, showing an advanced progress in ECG signal processing by DNN. Some basic neural architectures are further disclosed as an overview of the enhanced ECG representation of local and global rhythm information in deep layers, including: hybrid attention-based DNN (HADLN), embedding residual network (ResNet) and bidirectional Bi-LSTM architectures with attention mechanism to improve the interpretability of the model [ 42 ]; beat–interval–texture convolutional neural network (BIT-CNN) for image analysis of 2D time–morphology representations of the heartbeats (electrocardiomatrix) [ 43 ]; MultiFusionNet for multiplicative fusion of two DNNs trained on different sources of knowledge, including raw ECG data and large feature set from the Poincaré plot, average beat, cross correlation, fiducial points (intervals and amplitudes), presence of P-waves and atypical ventricular morphologies [ 44 ]; and an end-to-end 1D CNN with 10 convolutional blocks, two fully-connected layers, and an output Softmax classifier that uses only raw ECG input with data length normalization [ 45 ].…”
Section: Introductionmentioning
confidence: 99%